2012
DOI: 10.1002/bit.24430
|View full text |Cite
|
Sign up to set email alerts
|

Combining submerged electrospray and UV photopolymerization for production of synthetic hydrogel microspheres for cell encapsulation

Abstract: Microencapsulation within hydrogel microspheres holds much promise for drug and cell delivery applications. Synthetic hydrogels have many advantages over more commonly used natural materials such as alginate, however their use has been limited due to a lack of appropriate methods for manufacturing these microspheres under conditions compatible with sensitive proteins or cells. This study investigated the effect of flow rate and voltage on size and uniformity of the hydrogel microspheres produced via submerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 66 publications
1
64
1
Order By: Relevance
“…17 UV polymerisation is a common method for encapsulating cells in bulk gels and has been used with many cell types including chondrocytes 49 and mesenchymal stem cells 50 with high viability. Additionally, L929 fibroblasts that were encapsulated in the same PVA microspheres produced by a UV photopolymerisation and electrospray method also had >90% viability at 24 h. 8 Heparin has been incorporated into bulk hydrogels for the purpose of sustained growth factor release and presentation to cells and was shown to have beneficial effects on viability. 51 Therefore, it is likely that the heparin in the gels in the current study acts as a reservoir for growth factors present in the media (from the FBS) or released by the cells in the gel and helps to present these to the cells and in this way helps to sustain the viability.…”
Section: Cell Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…17 UV polymerisation is a common method for encapsulating cells in bulk gels and has been used with many cell types including chondrocytes 49 and mesenchymal stem cells 50 with high viability. Additionally, L929 fibroblasts that were encapsulated in the same PVA microspheres produced by a UV photopolymerisation and electrospray method also had >90% viability at 24 h. 8 Heparin has been incorporated into bulk hydrogels for the purpose of sustained growth factor release and presentation to cells and was shown to have beneficial effects on viability. 51 Therefore, it is likely that the heparin in the gels in the current study acts as a reservoir for growth factors present in the media (from the FBS) or released by the cells in the gel and helps to present these to the cells and in this way helps to sustain the viability.…”
Section: Cell Encapsulationmentioning
confidence: 99%
“…More recently, Young et al have reported on a novel electrospray method for producing synthetic hydrogel microspheres. 8 However the major issue with these techniques is the polydispersity of microspheres produced. Minimising the sphere polydispersity is particularly important for cell microencapsulation applications as size uniformity supports more controlled and predictable mass transport properties within the spheres, which is extremely important for cell function within the transplanted microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…28 This last approach has recently yield cell viability of more than 90% when combined with UV photopolimerization for cell encapsulation. 29 Regardless of the good perspective, most the authors report a lack of stability in the submerged electrospray when compared with the high stability and reproducibility of their counterparts in air. Quite often the solutions employed require stabilizing agents as surfactants.…”
Section: -1058/2012/6(4)/044104/19/$3000mentioning
confidence: 99%
“…Several parameters of this system were varied to 39 control the size and polydispersity of the microparticles, including the cell density, the flow rate and 40 the air pressure in the nozzle. The system was capable of producing cell-laden microparticles with an 41 average diameter of between 88.1 to 347.1 lm, and a dispersity of between 1.1 and 2.4, depending on 42 the parameters chosen. Varying the precursor flow rate and/or cell density was beneficial in controlling 43 the size and polydispersity of the microparticles; all microparticles exhibited very high cell viability, 44 which was not affected by these parameters.…”
mentioning
confidence: 99%